Cation and polyhedron substitution strategies: Effects on local crystal structure and on Bi3+ and Eu3+ co-doped inverse garnet phosphors' luminescence property. Issue 9 (1st May 2022) - Zhang, Ze; Mei, Lefu; Guo, Qingfeng; Liu, Ning; Liao, Libing
Abstract: Following the rapid growth of lightning technology, the development of red-emitting phosphors is effective for improving color temperature and color rendering index for w-LEDs devices. Herein, a single phased garnet phosphor with cation and polyhedron substitution modification was firstly prepared. For Mg3 Gd2 Ge3 O12 : Bi 3+, Eu 3+, the intensity has been remarkably improved by about 16% compared to the one without Bi 3+ sensitization. The energy transfer mechanism is identified in this work. Based on cation and polyhedron substitution strategies, novel phosphors with different compositions were obtained and further modified the PL properties. With Lu 3+ substitution, the bond lengths between Bi 3+ ion and anion ligands are decreased and the site symmetry has been strengthened, which leads to a 21 nm blue shift when Lu 3+ totally replaced Gd 3+ ions. In addition, Lu 3+ and [SiO4 ] substitution strategies both effectively increased symmetric rigid structure, which leads to a significant improvement in thermal stability, indicating the samples own great potential in optical applications This work provides a new insight to synthesis red-emitting phosphors for warm white-LEDs.